A multilevel investigation of antecedents of employee positive affective displays: the roles of customer negative affective displays and employee perceived supervisory support. Issue 3 (4th May 2017) - Tsai, Wei-Chi; Chen, Hao-Yi
ABSTRACT: Much past research on employee positive affective displays have explored their antecedents using a single level of analysis. The present study extends previous research by capturing the complex phenomenon of employee affective displays from a multilevel perspective. We used an event-sampling methodology to address a gap in the literature by examining affective displays at the intra-individual level and inter-individual level. Results based on 67 postal clerks completing 420 transactions in post offices in Taiwan show that customer negative affective displays were negatively correlated with employee positive affective displays. Moreover, employee perceived instrumental supervisory support had a cross-level moderating effect on the within-individual relationship between customer-displayed negative emotions and employee-displayed positive emotions. Specifically, those with perceived higher levels of instrumental supervisory support tended to express friendlier emotions while interacting with unhappy or angry customers than those with perceived lower levels of instrumental supervisory support. At the inter-individual level, results show that employee perceived emotional supervisory support was positively related to their affective displays at the aggregated employee level.